Crystallization and preliminary X-ray diffraction analysis of full-length spr1814, a response regulator of Streptococcus pneumoniae, in complex with a phosphoryl analogue - Park, Aekyung (International Union of Crystallography, 2014)
Spr1814 of Streptococcus pneumoniae is a signal transduction response regulator belonging to the NarL/FixJ subfamily, which has a helix–turn–helix DNA-binding effector domain. To understand how the phosphorylation of the conserved aspartic acid residue induces conformational changes in spr1814 allowing binding to the target promoter, recombinant spr1814 expressed in Escherichia coli was crystallized with the phosphoryl analogue beryllium fluoride BeF(3) (−) by the hanging-drop vapour-diffusion method. The crystals diffracted to 1.9 Å resolution and belonged to space group P2(1), with unit-cell parameters a = 40.2, b = 114.5, c = 50.1 Å, β = 92.1°. Structure determination by the SAD method using the bromine derivative 5-amino-2,4,6-tribromoisophthalic acid (B3C) is under way.